Genetic abnormalities leading to qualitative defects of sperm morphology or function. Issue 2 (9th December 2016) - Ray, P.F.; Toure, A.; Metzler‐Guillemain, C.; Mitchell, M.J.; Arnoult, C.; Coutton, C.
Abstract : Infertility, defined by the inability of conceiving a child after 1 year is estimated to concern approximately 50 million couples worldwide. As the male gamete is readily accessible and can be studied by a simple spermogram it is easier to subcategorize male than female infertility. Subjects with a specific sperm phenotype are more likely to have a common origin thus facilitating the search for causal factors. Male infertility is believed to be often multifactorial and caused by both genetic and extrinsic factors, but severe cases of male infertility are likely to have a predominant genetic etiology. Patients presenting with a monomorphic teratozoospermia such as globozoospermia or macrospermia with more than 85% of the spermatozoa presenting this specific abnormality have been analyzed permitting to identify several key genes for spermatogenesis such as AURKC and DPY19L2 . The study of patients with other specific sperm anomalies such as severe alteration of sperm motility, in particular multiple morphological anomalies of the sperm flagella (MMAF) or sperm unability to fertilize the oocyte (oocyte activation failure syndrome) has also enable the identification of new infertility genes. Here we review the recent works describing the identification and characterization of gene defects having a direct qualitative effect on sperm morphology or function. Abstract :